2019
DOI: 10.3892/etm.2019.7498
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Asiatic acid against pelvic inflammatory disease in rats

Abstract: Asiatic acid (AA) is one of the major components of the Chinese herb Centella asiatica and exerts a variety of pharmacological activities. However, the pharmacological effects of AA on pelvic inflammatory disease (PID) remain unknown. The purpose of the present study was to investigate the therapeutic efficacy and potential mechanisms of AA on PID in rats. A total of 75 female Sprague Dawley rats were randomly divided into the following five groups: A control group; a PID group; a PID + AA 5 mg/kg group; a PID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Emerging evidence suggests that NLRP3 inflammasome activation occurs in endometritis cells, while inhibiting NLRP3 inflammasomes generates a significant ameliorative role in the pathological process of endometritis [27]. Moreover, the activation of the NLRP3 inflammasome aggravates the degree of inflammatory infiltration in gynecological diseases such as endometritis and pelvic inflammatory disease, which indicates that therapeutic interventions via the NLRP3 inflammasome may be a novel strategy for treating PD [28,29]. Therefore further investigation is warranted to explore the role of the NLRP3 inflammasome in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that NLRP3 inflammasome activation occurs in endometritis cells, while inhibiting NLRP3 inflammasomes generates a significant ameliorative role in the pathological process of endometritis [27]. Moreover, the activation of the NLRP3 inflammasome aggravates the degree of inflammatory infiltration in gynecological diseases such as endometritis and pelvic inflammatory disease, which indicates that therapeutic interventions via the NLRP3 inflammasome may be a novel strategy for treating PD [28,29]. Therefore further investigation is warranted to explore the role of the NLRP3 inflammasome in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reasonable that pretreatment with asiatic acid alone apparently reduced inflammatory haemorrhage in vivo. Additionally, a recent study reported the effect of asiatic acid on decreasing the inflammatory reaction in cancer [15] . Therefore, effects on vascular integrity may play a role in the beneficial effects of asiatic acid in patients with APL.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, treatment with ATRA combined with asiatic acid did not exhibit a similar effect. One explanation is that asiatic acid blocks the oxidative stress induced by ATO in vascular ECs [ 48 , 15 ]; consequently, the activation or apoptosis of ECs is inhibited. Another possibility is that ATO caused more apoptosis in APL cells [49] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that NLRP3 inflammasome activation occurs in endometritis cells, while inhibiting NLRP3 inflammasomes generates a significant ameliorative role in the pathological process of endometritis [19]. Moreover, the activation of the NLRP3 inflammasome aggravates the degree of inflammatory infiltration in gynecological diseases such as endometritis and pelvic inflammatory disease, which indicates that therapeutic interventions via the NLRP3 inflammasome may be a novel strategy for treating gynecological diseases [20,21]. However, the role of the NLRP3 inflammasome in PD is still obscure, so further investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%